Description of Laccobius (s. str.) shengshanensis sp. n. from China (Coleoptera: Hydrophilidae) - Peng, Yunfei; Ji, Lanzhu; Bian, Dongju (Zootaxa, 2019)
The subgenus Laccobius (s. str.) Erichson, 1837 includes 25 species which are distributed in Palearctic (10 species) and Nearctic (15 species) regions (Hansen, 1999). The subgenus is characterized by the following diagnostic features: eyes in dorsal view nearly circular or slightly oval; hind tibiae evidently curved; elytral punctures arranged in about 20 longitudinal rows and all elytral punctures alike; and the mesoventral keel normally without lateral spurs, sometimes with a central swelling (Gentili, 1995).